Nilai Perusahaan Manufaktur Di Bursa Efek Indonesia Ditinjau Dari Perspektif Kebijakan Deviden Dan Kebijakan Hutang - Rohaeni, Nani; Hidayat, Syamsul; Fatimah, Ifat (Universitas Muhammadiyah Yogyakarta, 2018)
This study aims to determine how the influence of dividend policy and debt policy to corporate value. This research was conducted at a manufacturing company listed in Indonesia Stock Exchange (BEI) period 2012-2016. Sampling using Puropsive Sampling. A total of 13 manufacturing companies listed on the BEI to be sampled in this study. Regression analysis used in this study to see the effect of independent variables on the dependent variable either together or individually. The analysis results show that during the period 2012-2016 both dividend policy and debt policy have no significant effect on corporate value